Implementation of Storytelling Method on Students’ Speaking Skills in the Department of Occupational Therapy - Noerdjanah, Noerdjanah; Sugiono, Sugiono (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
Many students believe that speaking is one of the skills that is difficult to do considering that Indonesian people do not use English in their daily lives. In learning, lecturers should use learning methods that are fun, interactive, inspiring, and motivate students to actively participate according to their talents. One method that can be used is storytelling. Storytelling not only involves verbal skills, but also the ability to think critically, organize storylines, and interestingly convey information. This study aims to find out whether the storytelling method affects students’ speaking skills in the Department of Occupational Therapy. The research method used is an experimental quantitative research method with  One group Pre and Post post-test design. The sample involved 90 students of the Department of Occupational Therapy at the Ministry of Health of Surakarta. The data collection technique in this study is the tests. The results of the Wilcoxon test showed that the application of the storytelling method was proven to affect the speaking skills of students majoring in occupational therapy. In conclusion, the storytelling method significantly enhances the students’ speaking skills in the Department of Occupational Therapy.